2012
DOI: 10.1371/journal.pone.0048957
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure Induces Significant Changes in Nuclear Pore Complex of Human Cardiomyocytes

Abstract: AimsThe objectives of this study were to analyse the effect of heart failure (HF) on several proteins of nuclear pore complex (NPC) and their relationship with the human ventricular function.Methods and ResultsA total of 88 human heart samples from ischemic (ICM, n = 52) and dilated (DCM, n = 36) patients undergoing heart transplant and control donors (CNT, n = 9) were analyzed by Western blot. Subcellular distribution of nucleoporins was analysed by fluorescence and immunocytochemistry. When we compared prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…While our zebrafish data indicate a potential role for nucleoporins in cardiovascular development, these proteins are likely to function in adult heart as well, and ultimately, it is difficult to correlate phenotypes seen in fish with phenotypes one would see in a human. 38 …”
Section: Discussionmentioning
confidence: 99%
“…While our zebrafish data indicate a potential role for nucleoporins in cardiovascular development, these proteins are likely to function in adult heart as well, and ultimately, it is difficult to correlate phenotypes seen in fish with phenotypes one would see in a human. 38 …”
Section: Discussionmentioning
confidence: 99%
“…EXP-1 mediates the nuclear export of proteins, rRNA, snRNA, and some mRNAs. Previous studies in patients with ischemic cardiomyopathy showed elevated expression levels of both EXP-1 mRNA and protein, and interestingly, these levels were inversely related with ejection fraction and positively correlated with LVESD and LVEDD [5, 6], i.e . higher EXP-1 expression is linked with LV function impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that several molecules that participate in nuclear-cytoplasmic transport (Exportin-1 [EXP-1], IMP-β3, Nup160) are intimately related to a reduced left ventricular (LV) function in human HF. It has been found the transcriptomic signature of these alterations and has been identified that changes in gene expression, specifically of XPO1 that encodes EXP-1, were highly related to LV dysfunction in patients with HF of ischemic etiology [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically the transmembrane nucleoporin NDC1, the scaffold nucleoporin Nup160, and the nuclear basket nucleoporin Nup153 are increased in hearts of patients with ischemic and dilated cardiomyopathy, while Nup93 was increased only in dilated heart patients. NDC1 was also shown to be mislocalized in cardiomyocytes from both ischemic and dilated hearts [162]. Supporting these data, a point mutation in the scaffold nucleoporin Nup155 was sufficient to delocalize the nucleoporin from the NPC, which led to early sudden death due to atrial fibrillation.…”
Section: Npcs In Other Disordersmentioning
confidence: 91%